2019
DOI: 10.1200/jco.2019.37.15_suppl.5582
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of durvalumab with or without tremelimumab in patients with persistent or recurrent endometrial carcinoma and endometrial carcinosarcoma.

Abstract: 5582 Background: Monoclonal antibodies Durvalumab (D) and Tremelimumab (T) inhibit binding of programmed cell death ligand 1 (PDL1) to PD1 and inhibit activation of cytotoxic T-lymphocyte-associated protein 4 (CTLA4), respectively, resulting in improved tumor immunosurveillance. There is rationale to study D and DT based on recent genomic and tumor microenvironment evaluation of endometrial cancer (EC). Methods: Eligible patients (pts) were randomized to D or DT. Pts received D 1500 mg intravenously (IV) ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…[46][47][48] The interim results of an ongoing phase II study of durvalumab (anti-PD-L1) and tremelimumab (anti-CTLA-4) versus durvalumab alone in recurrent endometrial cancer previously treated with platinum-based therapy were reported for 56 enrolled patients. 49 Observed ORRs were modest for both arms (14.8% of patients treated with durvalumab monotherapy and 11.1% of patients treated with combination durvalumab with tremelimumab). Additional early-phase trials are evaluating the combination of nivolumab with ipilimumab (anti-CTLA-4; NCT03508570 and NCT02982486) therapy in advanced endometrial cancer.…”
Section: Combination Immunotherapymentioning
confidence: 87%
“…[46][47][48] The interim results of an ongoing phase II study of durvalumab (anti-PD-L1) and tremelimumab (anti-CTLA-4) versus durvalumab alone in recurrent endometrial cancer previously treated with platinum-based therapy were reported for 56 enrolled patients. 49 Observed ORRs were modest for both arms (14.8% of patients treated with durvalumab monotherapy and 11.1% of patients treated with combination durvalumab with tremelimumab). Additional early-phase trials are evaluating the combination of nivolumab with ipilimumab (anti-CTLA-4; NCT03508570 and NCT02982486) therapy in advanced endometrial cancer.…”
Section: Combination Immunotherapymentioning
confidence: 87%
“…The included studies were 14 phase I/II clinical trials and 1 randomized phase III trial ( 19 33 ). No phase IV trial was found.…”
Section: Resultsmentioning
confidence: 99%
“…CTLA-4 is an immune regulator expressed on regulatory T cells that prevents binding of CD28 and inhibits activation of cytotoxic T cells, which offers a second pathway to activate immune response to tumor cells ( Di Tucci et al, 2019 ). At a planned interim analysis, durvalumab alone and combined with tremelimumab produced modest responses (ORR 14.8% and 11.1%, respectively) in MSS and MSI-H patients ( Rubinstein et al, 2019 ). Phase III trials are summarized in Table 6 ( ClinicalTrials.gov ).…”
Section: Emerging Agents and Clinical Trialsmentioning
confidence: 99%
“…Durvalumab is also being studied in combination with the CTLA-4 inhibitor tremelimumab ( Rubinstein et al, 2019 ). CTLA-4 is an immune regulator expressed on regulatory T cells that prevents binding of CD28 and inhibits activation of cytotoxic T cells, which offers a second pathway to activate immune response to tumor cells ( Di Tucci et al, 2019 ).…”
Section: Emerging Agents and Clinical Trialsmentioning
confidence: 99%